The complexity of social participation and its variable effects on the health and wellbeing of people living in deprived Maltese neighborhoods. Issue 1 (1st January 2021) - Satariano, Bernadine
ABSTRACT: Social participation is considered as an aspect of social capital that creates opportunities of gathering with people in the neighborhood influencing health and wellbeing positively. However, few studies emphasize that it can operate in multiple dimensions within a community and that it can impact on health and wellbeing variably. Applying the theory of complexity, this study highlights that as much as it can help individuals beneficially it can also cause them to experience detrimental effects on their health and wellbeing. Using qualitative, in-depth interviews with participant and non-participant adults and children living in two deprived neighborhoods in Malta, this study contributes by emphasizing how features of social participation do not operate in a linear way but in an intricate, diverse, dynamic, and always evolving manner. Therefore, the effects of social participation on health and wellbeing are highly complex, dynamic across generations, and contingent to people and place.